ELECTRONIC HEALTH RECORDS: EVALUATION OF USABILITY BY THE NURSING TEAM - Janaína Verônica Lahm; Deborah Ribeiro Carvalho (Universidade Federal do Paraná, 2015)
This work aimed to evaluate the usability and the difficulties met by 99 nursing professionals using electronic health records. It is exploratory quantitative research, based on data collected in July - November 2013. The results show that 71% of the auxiliary nurses/nursing technicians and 70% of the nurses had not received specific training; 56% of the team, who stated that they had not received training experienced difficulty in using the system. Among the characteristics of usability of the electronic health record evaluated, suitability to the task stood out positively, while suitability to learning stood out negatively. The system evaluated, therefore, in spite of the advances arising from it, is still presented as complex to the user who has not received training, in spite of its having a consistent and interactive interface.